MAXIMIZING ENGLISH PROFICIENCY THROUGH SHORT-TERM INTENSIVE COURSES - Asyhar, Wildan Isna; Naf'ihima, Fika Ar-rizqi (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
This study investigates the effectiveness of a short-term intensive English course designed to improve English Proficiency Test (EPT) scores among postgraduate students at Universitas Islam Kadiri (UNISKA) Kediri. EPT at UNISKA mirrors the TOEFL structure and functions as a critical requirement for postgraduate academic standards. However, many students struggle to meet the required scores due to limited time and lack of targeted instruction. Drawing on theories of motivation (Goal Setting Theory, Achievement Goal Theory, and Behavioral Goal Setting Theory) and Kolb’s Experiential Learning Theory, this research implements a five-session course focusing on listening, structure and written expression, and reading comprehension. The study uses a pre-experimental one-group pretest-posttest design with 70 postgraduate participants. Findings show a significant improvement in students’ EPT scores after completing the course. The results highlight the potential of well-structured, short-term interventions in enhancing academic English proficiency in a time-efficient manner, particularly when tailored to learners' needs and supported by motivational strategies. This study offers practical insights for higher education institutions aiming to support postgraduate students in meeting English language proficiency standards.